Review of 5G and 6G applications for mobile wireless communication in the military environment - Miličević, Zoran M.; Bojković, Zoran S. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: This paper seeks to provide a review of the applications of the fifth (5G) and the next, the sixth (6G), generation of mobile wireless communications in the military environment.Methods: Analyzes and syntheses were used to consider various aspects, challenges, developments, and implementations of the fifth (5G) generation as well as the sixth (6G) generation mobile wireless communications for military purposes.Results: The background and the state of the art of 5G and 6G mobile wireless communications are presented. Next, 5G military impact and initiatives are described. The paper also presents future prospectives of 6G for its usage in the military. Finally, possible 6G military applications are presented.Conclusion: 5G had achieved the first deployment by 2020 and completed the first phase of its evolution in 2022. The 5G Advanced starts as a version towards the sixth generation in a way to find different solutions for implementation not only for commercial, but also for military purposes. With the platform approach to connectivity, 5G military networks contain different requirements, range of implementation options with spectral efficiency, latency, and reliability as primary performance metrics. Toward 6G, machine learning (ML) and artificial intelligence (AI) methods have proposed new approaches to modeling, design, optimization, and implementation in military systems.
Keywords: the fifth generation (5G) technology; 5G military initiatives; the sixth generation (6G) technology; 6G military applications